A systematic review of dementia focused assistive technology - Evans, Joanna; Brown, Michael; Coughlan, Tim; Lawson, Glyn; Craven, Michael P. (Springer Verlag, 2015)
This paper presents a systematic review which explores the nature of assistive technologies currently being designed, developed and evaluated for dementia sufferers and their carers. A search through four large databases, followed by filtering by relevance, led to the identification and subsequent review of papers. Our review revealed that the majority of research in this area focuses on the support of day-to-day living activities, safety monitoring, memory aids and preventing social isolation. We conclude that the majority of AT currently available support day-to-day living activities, safety monitoring and assisting healthcare. However these devices merely address the ‘ease of living’ rather than focusing on ‘quality of life’. Although there are some devices which address social symptoms of Dementia, few address behavioural issues such as aggression and virtually none are available to support recreational activities. After discussing the implications of these findings, we finally reflect on general design issues for assistive technologies in this domain that became apparent during the review.